(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the terms related to kinship in Uzbek and Korean. The history of the origin of relationship-related words, their similarities and differences, and their levels of use in speech have been extensively discussed. During the study it was found that both languages have many similar aspects. It was concluded that not only kinship but other areas of the two languages should be studied extensively.